3D printability of ternary Portland cement mixes containing fly ash and limestone. (2022) - Dey, Dhrutiman; Srinivas, Dodda; Boddepalli, Uday; Panda, Biranchi; Gandhi, Indu Siva Ranjani; Sitharam, T.G.
Abstract: This paper reports the influence of limestone, by partial replacement of fly ash, on the fresh properties, printability, and interlayer bond strength of 3D printed high volume fly ash mortar. Limestone powders at replacement levels between 0 and 15% (mass basis) were used to proportion ternary binder formulations. The incorporation of limestone alters fresh properties like slump, slump flow, yield stress. It was observed from the results of 3D printing test that ternary mixes with limestone demonstrates higher buildability. Based on the material relative deformation at different times and concurrent printing, the effect of mix designwas linked to the printing performance. The results of interlayer bond strength revealed that bond strength decreases with increase in limestone dosage. It was observed that the bond strength for the high buildable mix in the bottom layers was lower followed by middle and top layers. This is due to an overestimation of bond strength caused by X-directional porosity (i.e. printing direction) resulting from increased nozzle standoff distance induced by bottom layer suppression.